Reforming social regulation - "Graymer, Le Roy(ed.) ; Thompson, Frederick(ed.)" (London, 1982)
Over the past two decades, the federal government has intervened actively in our lives to safeguard the air we breathe, the water we drink, the drugs and other products we consume, and our occupational health. Yet many of the policies and regulations imposed to reach these socially desired goals have been inefficient, inappropriate, and sometimes even counterproductive. Reforming Social Regulation goes beyond traditional critiques of the regulatory process to suggest creative and constructive ways to achieve the objectives of the new social regulation. The contributors, sixteen eminent scholars, policymakers, and analysts, identify and diagnose problems associated with the existing regulatory regime, examine recent efforts to rationalize the system, and discuss the political feasibility of reforming and improving the regulatory enterprise. Their insightful analyses and suggestions will benefit those concerned with public policy analysis and administration, planning, law, environmental science, political science, economics, and business.
Keywords: Social legislation